Sosialisasi Tabungan Emas sebagai Sarana Investasi Bagi Ibu Rumah Tangga RT 08 RW 15 Kel. Meteseh Kota Semarang - Asah Wiari Sidiq; Ahmad Sahri Romadon; Citra Rizkiana (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Gold savings is a type of savings in the form of gold measured in grams, which can increase or decrease over time. The balance of gold savings can be exchanged for gold bars based on the number of gold grams in the account, such as 1 gram, 2 grams, or multiples thereof. The purpose of this gold savings socialization is to provide in-depth knowledge and understanding to housewives about the benefits of gold savings as an investment tool. The service partner consists of 20 housewives from RT 08 RW 15, Meteseh Village, Semarang City. The community service method includes preparation, implementation, evaluation, and reporting. The preparation phase involved gathering information, determining the theme, and organizing the material for the activity. The implementation of PKM involved providing education through lectures, Q&A sessions, discussions, and simulations on gold savings knowledge. The evaluation phase consisted of administering pre-test and post-test questionnaires and preparing a final report. The results of the Community Service implementation, based on the evaluation of pre-test and post-test for the housewives of RT 08 RW 15, showed an improvement in knowledge and understanding of gold savings, from 36.25% in the pre-test to 66.75% in the post-test.